Third five year plan - India (New Delhi : Govt. of India, Planning Commission, 1961)
India's Third Five- Year Plan (1961-66) was published on July 6, 1960 by the Planning Commission. The Size of the Plan: The Plan envisages a total outlay of Rs. 11,250 crores (of which Rs. 7,250 crores in the public sector and Rs. 4,000 crores in the private sector) as compared with the Second Plan outlay of Rs. 7,700 (of which Rs. 4,600 crores in the public sector and Rs. 3,100 crores in the private sector.
Includes index.
lje 14/12/18
Loans
Keywords: Economic plan; Economic policy; Economic development; India